Characterizing Inequities in Pediatric Appendicitis Delayed Diagnosis and Perforation - Stephen Trinidad, MD, MPH; Raphael Parrado, MD; Amelia Gavulic, BS; Mindy Hoang, BS; Qing Duan, PhD; Kevin M. Overmann, MD, MS; Ndidi Unaka, MD, MEd; Andrew F. Beck, MD, MPH; Meera Kotagal, MD, MPH (Elsevier, 2024)
Objective: We sought to characterize the impact of a child's sociodemographic characteristics on their odds of delayed diagnosis and perforation in pediatric appendicitis. Study design: We performed a single-center, retrospective cohort study of all pediatric appendicitis admissions between 2016 and 2021. Using a multivariable model, we evaluated for associations between delayed diagnosis and perforation and a child's sociodemographic characteristics, including their age, sex, race and ethnicity, insurance status, and their home census-tract Material Community Deprivation Index value. Results: The study included 3248 patients. The median age was 12.1 years (IQR 9.5-14.9 years). Most patients were male (60.3%), identified as non-Hispanic White (78.0%), and had private insurance (55.4%). The delayed diagnosis and perforation rates were 6.4% and 25.1%, respectively. Delayed diagnosis cases had a greater perforation rate (56% compared with 21.5%, P < .001). On adjusted analysis, older age decreased the odds (OR 0.91, CI 0.87-0.94) of delayed diagnosis, whereas female sex (OR 1.50, CI 1.13-2.00) and socioeconomic disadvantage (OR 1.56 for quartile 4 vs quartile 1, CI 1.00-2.43) increased the odds. Furthermore, older age (OR 0.91, CI 0.89-0.93) decreased the odds of perforation, whereas non-Hispanic Black (OR 1.72, CI 1.3-2.29) or Hispanic (OR 1.60, CI 1.24-2.08) compared with non-Hispanic White identification and socioeconomic disadvantage (OR 1.43 Q4 vs Q1, CI 1.12-1.83) increased the odds. Conclusions: Our reported delayed diagnosis rate is greater than recent literature, highlighting the need to consider visits that occur across different health care settings. We further identify sociodemographic factors, including socioeconomic status, that impact a child's risk of delayed diagnosis and perforation.